Implementasi Konsep Benchmarking untuk Meningkatkan Kinerja Institusi Pendidikan - RUSLAN; Aminah, Siti (Al-Mutharahah: Jurnal Penelitian dan Kajian Sosial Keagamaan, 2025)
Abstract This study aims to gain new insights that can serve as a reference for academics and education practitioners in formulating policies oriented toward optimizing the concept of benchmarking to improve the performance of educational institutions. Benchmarking has been proven to be an effective method for improving the performance of educational institutions. However, its success heavily depends on institutional readiness, stakeholder involvement, and continuous evaluation. The implementation of benchmarking faces various challenges, such as the lack of institutional preparedness for change, limited resources, and difficulties in obtaining valid and relevant comparative data. Other challenges include minimal stakeholder involvement and the absence of continuous evaluation. To overcome these obstacles, clear strategies, strong support from various parties, the use of technology, and inter-institutional collaboration are required. The selection of an appropriate type of benchmarking is also a key factor in ensuring success. Competitive benchmarking helps institutions enhance their academic competitiveness by comparing their performance with direct competitors. Functional benchmarking focuses on specific aspects, such as teaching methods or curriculum management, to improve operational efficiency and service quality. Meanwhile, internal benchmarking enables institutions to compare performance across units or departments to identify best practices internally before seeking external comparisons. In addition to adopting best practices from other institutions, it is essential for educational institutions to maintain their unique characteristics and distinctive culture. Benchmarking is not merely a process of imitation but a means to develop institutional potential and identity to remain competitive without losing the qualities that make them unique. With a structured, continuous, and institution-specific approach to benchmarking, this method can serve as an effective strategy for improving the long-term performance of educational institutions. Keywords: Benchmarking, educational institution performance Abstrak Penelitian ini bertujuan untuk memperoleh wawasan baru yang dapat menjadi rujukan bagi akademisi dan praktisi pendidikan dalam merumuskan kebijakan yang berorientasi pada optimalisasi konsep benchmarking dalam meningkatkan kinerja institusi pendidikan. Benchmarking telah terbukti sebagai metode yang efektif dalam meningkatkan kinerja institusi pendidikan. Namun, keberhasilannya sangat bergantung pada kesiapan institusi, keterlibatan stakeholder, serta evaluasi yang berkelanjutan. Implementasi benchmarking menghadapi berbagai kendala, seperti kurangnya kesiapan institusi terhadap perubahan, keterbatasan sumber daya, serta kesulitan dalam memperoleh data pembanding yang valid dan relevan. Tantangan lain yang dihadapi adalah minimnya keterlibatan stakeholder dan evaluasi yang tidak berkelanjutan. Untuk mengatasi hambatan ini, diperlukan strategi yang jelas, dukungan dari berbagai pihak, serta pemanfaatan teknologi dan kerja sama antar lembaga. Pemilihan jenis benchmarking yang sesuai juga menjadi faktor kunci keberhasilan. Benchmarking kompetitif membantu institusi meningkatkan daya saing akademik dengan membandingkan kinerja dengan pesaing langsung. Benchmarking fungsional berfokus pada aspek tertentu, seperti metode pengajaran atau manajemen kurikulum, guna meningkatkan efisiensi operasional dan kualitas layanan. Sementara itu, benchmarking internal memungkinkan institusi membandingkan kinerja antar unit atau departemen di dalamnya untuk mengidentifikasi praktik terbaik secara internal sebelum mencari perbandingan eksternal. Selain mengadopsi praktik terbaik dari institusi lain, penting bagi lembaga pendidikan untuk mempertahankan ciri khas dan budaya unggulnya. Benchmarking bukan sekadar proses meniru, melainkan sarana untuk mengembangkan potensi dan identitas institusi agar tetap kompetitif tanpa kehilangan karakter yang telah menjadi keunggulan. Dengan penerapan benchmarking yang terstruktur, berkelanjutan, dan disesuaikan dengan karakteristik masing-masing institusi, metode ini dapat menjadi strategi yang efektif dalam meningkatkan kinerja lembaga pendidikan dalam jangka panjang. Kata Kunci: Benchmarking, kinerja institusi pendidikan